KORELASI INDEKS MASSA TUBUH DENGAN TEKANAN DARAH PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS RIAU ANGKATAN 2012 DAN 2013 - Pratama, Bayu Fajar; Christianto, Erwin; Bebasari, Eka (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTObesity is now recognized as one of most prevalent disease world-wide in both developed and developing countries. Body mass index (BMI) is the most simple and common index to describe body fat. Obesity can cause higher risk of cardiovascular disease, such as hypertension. The purpose of this study was to determine correlation between BMI and blood pressure. The design of this study was analytic cross sectional. Population of this study were all students of Medical Faculty of Riau University batch 2012 and 2013. Sampling technique used in this study was total sampling. Sample of this study were 242 students. The result of this study was 47,93% of subjects had normal BMI and 40,09% of subjects were overweight and obese. According to systolic blood pressure, 63,22% of subjects had normal systolic blood pressure and 36,78% of subjects were pre-hypertension and hypertension. According to diastolic blood pressure, 64,46% of subjects had normal systolic blood pressure and 35,54% of subjects were pre-hypertension and hypertension. This study showed there was significant positive correlation between BMI and blood pressure which the power of correlation was weak for BMI and systolic blood pressure (r = 0,302; p = 0,000) and the power of correlation was very weak for BMI and diastolic blood pressure (r = 0,171; p = 0,008).Keywords: body mass index, blood pressure